Enhancing anaerobic digestion of palm oil mill effluent (POME) by addition of cao derived from waste cockle shell as a buffering solution in an upflow anaerobic sludge blanket (UASB) reactor - Mohamad Mokhtar, Ibrahim (2023)
Various methods have been studied for the treatment of Palm Oil Mill Effluent (POME). However, not all of the treatment methods are suitable and efficient in POME treatment. The Upflow Anaerobic Sludge Blanket (UASB) reactor could be utilised to treat a high-strength wastewater such as POME and a higher Chemical Oxygen Demand (COD) removal efficiency and a good methane production rate could be achieved. In the anaerobic digestion of POME, optimum pH should be maintained to ensure the anaerobic process degrades organic matter effectively. The potential of utilizing waste into suitable buffering solutions or neutralization agent could lead to an inexpensive and economically viable approach. To date, there is still a lack of research discussing the potential of using waste cockle shells as a neutralization agent for POME treatment. Thus, this study is designed to evaluate the impact of adding a buffering solution containing calcium oxide (CaO) derived from waste cockle shells on the performance of the continuous UASB reactor treating POME. Overall, four phases were involved in achieving the main objective; i) establishing the correlation between calcination’s operating parameters of waste cockle shells and CaO yield. ii) study the impact of adding calcined cockle shells (CCS) on biomethane production and anaerobic treatability of synthetic wastewater and POME .iii) a kinetic and microbial study was conducted on the UASB reactor treating POME with the addition of CCS. iv) evaluating the biohydrogen production via a dry reforming (DR) process fed with biomethane produced from anaerobic digestion of POME in the continuous UASB reactor. Once the calcination’s operating parameters of obtaining the CCS containing the highest CaO (temperature 900°C, 97.57% CaO) were established, the CCS was dissolved in water (between 1 and 15 g/L concentrations) before the utilization as a buffering solution in the anaerobic digestion of POME. The impact of adding CCS in various concentrations during the anaerobic digestion of POME in the UASB reactor operated at various organic loading rate (OLR) (0.3 to 13.4 g COD/L.day), hydraulic retention time (HRT) (1 to 6 day) and different temperature (28 and 38ºC) fed with i) synthetic wastewater containing chemical oxygen demand (COD) concentrations between 1,665 and 3,416 mg/L, ii) POME with COD concentrations of 1030 and 40,460 mg/L was evaluated. The impact of adding CCS in comparison with commercial Na2CO3 was also determined. The result indicated that adding CCS during the anaerobic digestion of synthetic wastewater has enhanced the COD removal up to 92.35% compared with commercial Na2CO3 (79.36%). In comparison with the UASB reactor treating synthetic wastewater, the utilization of CCS in treating POME has improved the COD removal at about 6% (98% compared to 92%) and promoted the continuous production of biogas between 14 and 22 L/d at OLR of 7 to 14 g COD/L.day. As for synthetic wastewater, minimal biogas production was recorded. The biokinetic parameters evaluated on the UASB reactor treating POME with the addition of CCS were the growth yield (YG), 3.906 g VSS/g CODremoved.d; the specific biomass decay (b), 0.233 d-1; the specific biomass growth rate (μmax), 1.861 d-1; and the saturation constant (Ks), 3.459 g-COD/L. Using the 16S ribosomal ribonucleic acid (rRNA) cloning technique, the genus methanosarcina and methanosaeta were dominant methanogens found in both feeding schemes in the UASB reactor. Overall, the microbial population (Bacteria and Archaea) in POME as the substrate is more diverse than synthetic wastewater due to the abundance of microorganism population in raw POME, which was used as a substrate. The result also shows that the dry reforming converted biogas into 83 % of H2, and 100% CH4 conversion was recorded. In conclusion, using CCS as a buffering solution has proven to improve the anaerobic digestion of POME in a continuous UASB reactor in terms of COD removal efficiency and the biogas production rate. The evaluated biokinetic parameters could be utilized for predicting the performance of the anaerobic digestion of POME using the UASB reactor. The potential of using molecular biology techniques to provide a detailed profile of the microbial community structure will enhance the optimization of treatment processes and eventually produce acceptable effluent quality.